Nervous system drug delivery : principles and practice - Lonser, Russell R.; Sarntinoranont, Malisa; Bankiewicz, Kristof (Academic Press, 2019)
Nervous System Drug Delivery: Principles and Practice helps users understand the nervous system physiology affecting drug delivery, the principles that underlie various drug delivery methods, and the appropriate application of drug delivery methods for drug- and disease-specific treatments. Researchers developing nervous system putative therapeutic agents will use this book to optimize drug delivery during preclinical assessment and to prepare for regulatory advancement of new agents. Clinicians will gain direct insights into pathophysiologic alterations that impact drug delivery and students and trainees will find this a critical resource for understanding and applying nervous system drug delivery techniques. Offers an up-to-date, comprehensive resource on drug delivery to the nervous systemProvides a bridge for understanding across nervous system delivery-related physiology, drug delivery principles. and the methodologies that underlie the various methods of drug distribution (with clinical application)Written for a broad audience of researchers, clinicians and advanced graduate students in neuroscience, neurology, neurosurgery, pharmacology, radiology and psychiatry